10 teses sobre experiência e educação: leituras deleuzianas - Barros, Gustavo de Almeida (2020)
This survey has an analytical theoretical and bibliographic incuse, and aims at discussing about the concept of experience present in the French philosopher Gilles Deleuze’s thought and about his distinction before the classical conception of the experience present in a traditional empiricism; and how the concept takes place before its use inside education. That conception emergency has been built since the National Common Curricular Base established the Experience Fields as a practice in Childhood Education. Our text is divided in three parts, of which the first one did an analysis on the monographs written by Deleuze about the philosophers Baruch de Spinoza, David Hume, Immanuel Kant, Henri Bergson and Friedrich Nietzsche. Except Kant, who is criticized and will have the reputation of transcendental changed and turned proper, the others inspired his thought, occurring in his individual production and in his partnership with the psychoanalyst Felix Guattari. In the second part, we deal with the epistemological conjectures of education and how the experience is built from them. We made a judgment about the conception that the School elaborates on the experience in its practices, so that we purpose what would be an Experience Education, by having Deleuze’s conceiving of experience as the focal point and the practice of such education. In the third and last part, we presented ten theses about the conception of experience on Deleuze and education, concluding, for us, the possible form of consider the experience on the way purposed by Deleuze, so that education reinforce the bodies to create new forms of existence.